Identitas Budaya Jawa dalam Lagu Denny Caknan: Studi Visual Culture - Bayujati Prakoso (CHRONOLOGIA, 2023)
In the midst of being exposed to music in foreign languages, the local music industry must grow as a form of strengthening the love for the nation's cultural products. Javanese songs as a form of cultural expression are also experiencing an increase in popularity. The popularity of a song cannot be separated from the use of language in the lyrics, as well as the arrangement of the song's video clip, which is a vital aspect in the production of the song. The nation's local songs in Javanese include songs from Denny Caknan. This study seeks to analyze the Javanese cultural identity in Denny Caknan's song. This study uses a qualitative approach, and the theory of Visual Culture. The results of the research show that Denny Caknan wants to visualize Javanese cultural identity through his songs. The visualized Javanese cultural identity, namely iconic places, tourist attractions in Java, the use of typical Javanese clothing, ontel bicycles, jatilan dances, and the selection of lyrics which are dominated by the Javanese language are one of the Javanese cultural identities that are depicted in Denny Caknan's songs. . The packaging of Denny Caknan's song by sharing it on the YouTube channel and Instagram social media, makes people more aware of the values, identity and symbols of Javanese culture. From this research it was found that Denny Caknan's songs are Indonesian cultural products which are used as a means of reinforcing the values of nationalism in Indonesian society, and increasing love for the nation's culture. This marks the socialization of Javanese cultural identity through Denny Caknan's songs. Apart from that, the use of the Javanese language combined with Indonesian in some of the songs aims to introduce to the general public the value of Javanese culture in terms of language.